Epiblepharon in congenital glaucoma: case–control study. Issue 12 (28th March 2017) - Kim, Namju; Yoo, Yung Ju; Choung, Ho-Kyung; Khwarg, Sang In
Abstract : Background/aims: To assess the prevalence, clinical features and risk factors of lower lid epiblepharon among patients with congenital glaucoma. Methods: Cross-sectional, observational, case–control study. Patients diagnosed with congenital glaucoma between August 1999 and November 2014 were included. Demographic and clinical characteristic data were collected. Age-matched normal controls were recruited form general population. Main outcome measures were the prevalence, laterality and factors associated with epiblepharon in patients with congenital glaucoma. Results: The prevalence of lower lid epiblepharon was higher in patients with congenital glaucoma compared with control group (40.7% vs 13.3%, p<0.001). Unilateral epiblepharon was only shown in patients with congenital glaucoma (47.8% vs 0.0%, p<0.001). Multivariate analysis revealed that high intraocular pressure (IOP) at glaucoma diagnosis (OR=1.122), presence of corneal erosion (OR=82.664) and presence of buphthalmos (OR=12.600) were significantly associated with the presence of lower lid epiblepharon. In addition, unilateral epiblepharon was associated with unilateral buphthalmos and unilateral glaucoma (OR of 49.849 and 7.338, respectively). Conclusions: The prevalence of epiblepharon was higher in patients with congenital glaucoma compared with age-matched general population. In patients with congenital glaucoma, epiblepharon was associated with corneal erosions. In addition, buphthalmos and initial high IOP were associated with the development of lower lid epiblepharon. More importantly, unilateral buphthalmos was also significantly associated with unilateral epiblepharon. Therefore, in patients with congenital glaucoma, presence of epiblepharon should be evaluated especially in patients accompanying buphthalmos or corneal erosion.